The Relationship Between the Length of Use of Implantable Contraceptives with Changes in Acceptor Weight - Dewi Lestari Sayem; Rani Safitri; Nila Widya Keswara (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Weight gain in contraceptive implant acceptors can have various negative health impacts, including degenerative diseases such as heart disease, hypertension, and a reduced ability to carry out daily activities. This study aimed to examine the relationship between the duration of contraceptive implant use and weight gain among women of reproductive age. A quantitative design with a cross-sectional approach was applied. The study population consisted of all contraceptive implant acceptors registered at the health facility, totaling 74 respondents. The sampling technique used was random sampling to ensure representativeness. The independent variable in this research was the duration of contraceptive implant use, while the dependent variable was weight change. Data were collected using a structured questionnaire, and statistical analysis was performed using the chi-square test. The results revealed a statistically significant relationship between the duration of contraceptive implant use and weight gain among respondents. Specifically, the longer the duration of implant use, the higher the likelihood of experiencing weight gain. This finding supports existing evidence that hormonal contraceptive implants may cause side effects, including increased body weight. If not properly managed, such weight gain can lead to overweight or obesity, conditions that substantially raise the risk of developing metabolic disorders such as diabetes mellitus, as well as cardiovascular diseases including hypertension and coronary heart disease. Based on these results, it is recommended that contraceptive implant users undergo regular weight monitoring to identify changes early. Additionally, health education programs emphasizing balanced nutrition and adequate physical activity should be implemented for women using hormonal contraceptives. Health care providers are encouraged to deliver comprehensive counseling prior to implant insertion, ensuring that potential side effects and preventive measures are clearly explained. Such proactive steps will help women make informed decisions and maintain optimal health while using contraceptive implants.